2010
DOI: 10.1111/j.1460-9592.2009.03237.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for deep venous thrombosis after idiopathic scoliosis surgery in children: a pilot study

Abstract: Thromboembolic event seems to be rare after scoliosis surgery. Prophylaxis for venous thrombosis should not be recommended in such patient. But, larger series are required to confirm such results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…A limitation of this study is that we did not investigate postoperative VTE using modalities such as MDCT or ultrasonography in the adolescent patients because the incidence of VTE after spinal surgery is very few in this age group [4,5] . The other limitations are that the same spinal surgery in adolescent and old patients was not undergone and the sample size was relatively small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation of this study is that we did not investigate postoperative VTE using modalities such as MDCT or ultrasonography in the adolescent patients because the incidence of VTE after spinal surgery is very few in this age group [4,5] . The other limitations are that the same spinal surgery in adolescent and old patients was not undergone and the sample size was relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, the reported incidence of symptomatic PE is 0.6% [3] and that of asymptomatic VTE is 19% (DVT 5%, PE 18%) [3] . The incidence of VTE after spinal surgery in adolescent patients [4,5] , as in younger children [6,7] , is very few compared with the incidence among older patients. It is not known how blood coagulation and fibrinolysis, which are related to VTE, change after spinal surgery in adolescent patients, whereas a few studies have investigated those changes in older patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are sporadic reports of DVT in adults undergoing such ligament reconstruction as an outpatient, the routine use of chemoprophylaxis, especially in patients younger than 40 years without additional risk factors is not recommended. 49 In addition, we had 7 cases of VTE associated with musculoskeletal infections, including osteomyelitis secondary to MRSA. Other authors have also described such association, with some cases diagnosed even before surgical resection of the bony exostoses.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound has been reported as a complementary tool during preoperative evaluation not only to assess cardiac function but also to detect pulmonary edema, identify a pleural effusion, examine the airway, 14 evaluate stomach content, 15 assess diaphragmatic motion, 16 and rule out deep vein thrombosis. 17 In a retrospective study, a group based in Melbourne Australia showed that patients admitted with hip fractures who underwent a focused transthoracic ultrasound had lower mortality than a control group. 18 Prospective studies should be undertaken to confirm these findings in similar settings.…”
Section: Preoperative Evaluationmentioning
confidence: 99%